2021
DOI: 10.1007/978-3-030-72113-8_1
|View full text |Cite
|
Sign up to set email alerts
|

Stay on Topic, Please: Aligning User Comments to the Content of a News Article

Abstract: Social scientists have shown that up to 50% of the comments posted to a news article have no relation to its journalistic content. In this study we propose a classification algorithm to categorize user comments posted to a news article based on their alignment to its content. The alignment seeks to match user comments to an article based on similarity of content, entities in discussion, and topics. We propose a BERTAC, BERT-based approach that learns jointly article-comment embeddings and infers the relevance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Overwhelmingly, we found that most comments were neither about horse-race or policy, supporting research that shows that a majority of comments on news stories are unrelated to the journalistic content [15]. This is troubling but unsurprising because it suggests people are not using news sites to comment or discuss the election in meaningful ways.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Overwhelmingly, we found that most comments were neither about horse-race or policy, supporting research that shows that a majority of comments on news stories are unrelated to the journalistic content [15]. This is troubling but unsurprising because it suggests people are not using news sites to comment or discuss the election in meaningful ways.…”
Section: Discussionsupporting
confidence: 72%
“…Election coverage frequently falls neatly into either horse-race or policy categories [3] [4], but our data showed that online discussions clearly do not. This is unsurprising but informative because online commenters often veer off-topic [15]. Examples of comments that fit into "neither" included nonsensical content (e.g., "whaaaaaa.....whaaaaaaaaaa"), responses to other commenters that had little content (e.g., "LOL"), impolite speech (e.g., "F OFF LOSER"), and off-topic content (e.g., "Did Katy Perry jump off a NY skyscraper this morning?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many practical problems, humans do not agree on their annotations [4], providing noisy labels that affect the downstream performance of machine learning models [8]. One such problem is the Article-Comment Alignment Problem (ACAP) [2], where the goal is to classify an article-comment pair into one of several categorical relevancy levels. For example, an annotator might consider article-comment pairs relevant, while another might consider them irrelevant.…”
mentioning
confidence: 99%